The Absolute Number of Oligodendrocytes in the Adult Mouse Brain - Valério-Gomes, Bruna; Guimarães, Daniel M.; Szczupak, Diego; Lent, Roberto (Frontiers in Neuroanatomy, 2018)
The central nervous system is a highly complex network composed of various cell types, each one with different subpopulations. Each cell type has distinct roles for the functional operation of circuits, and ultimately, for brain physiology in general. Since the absolute number of each cell type is considered a proxy of its functional complexity, one approach to better understand how the brain works is to unravel its absolute cellularity and the quantitative relations between cell populations; in other words, how one population of cells is quantitatively structured, in relation to another. Oligodendrocytes are one of these cell types – mainly, they provide electric insulation to axons, optimizing action potential conduction. Their function has recently been revisited and their role extended, one example being their capability of providing trophic support to long axons. To determine the absolute cellularity of oligodendroglia, we have developed a protocol of oligodendrocyte quantification using the isotropic fractionator with a pan-marker for this cell type. We report a detailed assessment of specificity and universality of the oligodendrocyte transcription factor 2 (Olig2), through systematic confocal analyses of the C57BL/6 mouse brain. In addition, we have determined the absolute number (17.4 million) and proportion (about 20%) of this cell type in the brain (and in different brain regions), and tested if this population, at the intraspecific level, scales with the number of neurons in an allometric-based approach. Considering these numbers, oligodendrocytes proved to be the most numerous of glial cells in the mouse brain.